PRELIMINARY PHYTOCHEMICAL SCREENING AND EVALUATION OF ANALGESIC AND MUSCLE RELAXANT ACTIVITY OF THE ETHANOLIC EXTRACT OF THE LEAVES OF MIRABILIS JALAPA - BHARALI, DEEPSIKHA; SAHA, DIPANKAR (International Journal of Current Pharmaceutical Research, 2017)
Objective: The aim and objectives of the present work is to determine pharmacological activity upon ethnopharmacological survey. The present study deals with phytochemical screening and analgesic as well as muscle relaxant activity of leaves of Mirabilis jalapa. Methods: The present study is aimed at phytochemical screening and evaluating the analgesic and muscle relaxant activities of ethanolic leaf extract of Mirabilis jalapa by using hot plate method and rota rod method respectively [1, 2]. The Phytochemical screening of the extract was done according to the standard procedures to reveal the presence of the active constituents like Alkaloids, flavonoids, phenols, glycosides, tannins, saponins, steroids, carbohydrates etc [3-5]. Results: The analgesic and muscle relaxant activity study were dose dependent. The EEMJ extracts (100 mg/kg, 200 mg/kg, 500 mg/kg) and the standard drug Diclofenac sodium (25 mg/kg) shows significant increase in the reaction time when compared with control at 30 min, 60 min, 90 min and 120 min and the effect of standard was found to be highest during the study. Another study was designed to evaluate the skeletal muscle relaxant properties of ethanolic extract of leaves of Mirabilis jalapa. Linn by taking the EEMJ extracts (100 mg/kg, 200 mg/kg, 500 mg/kg) and standard drug Lorzepam (10 mg/kg). Both the extracts and standard drug show decrease in the fall of time in a dose dependent manner when compared with control at 15 min, 30 min, 45 min respectively. Conclusion: Therefore, from the above study it is revealed that Mirabilis jalapa showing better pharmacological activities (Analgesic and Muscle relaxant) in dose dependent manner.